Experimental study of resin coating to improve the impact strength of fused filament fabrication process pieces. Issue 3 (27th February 2021) - López Taborda, Luis Lisandro; Pérez, Eduar; Quintero, Daniel; Noguera Polania, José Fernando; Zambrano Rodriguez, Habib; Maury, Heriberto; Esparragoza, Ivan E.
Abstract : Purpose: This study aims to evaluate the impact breaking energy of the parts manufactured by the fused filament fabrication (FFF) method. The evaluation considers the use of the epoxy resin coating, different materials and different printing orientations. Design/methodology/approach: The authors developed an experimental statistical design using 54 experimental trials. The experiments' output variable is the impact break energy of the parts manufactured by the FFF method. The input variables for the experiments consist of an epoxy resin coating (XTC-3D®, generic resin and without resin coating), different filament materials (nylon + carbon fiber, polyethylene terephthalate and polycarbonate) and different printing orientations (flat, edge and vertical) used. The authors carried out the tests following the EN ISO 179-1. Findings: The use of resin coating has a significant influence on the impact energy of parts manufactured using the FFF method. The resin coating increases the impact resistance of parts processed by FFF by almost 100% of the value as compared to the parts without a resin coating. Post-processing is useful on ductile materials and increases impact breaking energy at weak print orientations. Originality/value: This research opens a new opportunity to improve the mechanical properties of parts manufactured using the FFF method. The use of a resin coating reinforces the parts in weak print orientation.